The Relationship between the Interest in Poetry and the Degree of Sensivity: A Primary Study of Sample of Khorasan-Iran Students - Moqaddam, Reza Naqavi (PAROLE: Journal of Linguistics and Education, 2019)
This study attempts to find a relation between the amount of interest in poetry and the degree of sensitivity, especially among the college students. If a positive correlation can be found, scholars and teachers may be able to offer students with weak perception of the environment, poetry reading. Dr. Elaine N. Aron’s questionnaire, Highly Sensitive Person Scale 2007, was the tool of this paper to evaluate the hypersensitivity of students, the results of which were tested correlation with a number of five questions that was added to the original questionnaire. The added questions were to demonstrate the students’ interest or disinterest toward poetry, and through Pearson Product-Moment Correlation Coefficient and independent Samples T-Test it became possible to calculate the correlation of sensitivity tests and the interest in poetry. The results answered research questions, and it was found that except the question number five, there was no significant relationship between sensitivity and the other variables. However, the question number five which showed a positive relationship between sensitivity and the amount of empathetic understanding of those who are interested in poetry, could indicate a meaningful correlation by reminding that empathy is an equivalence of unconscious admittance